Overview of elagolix for the treatment of endometriosis. (3rd May 2016) - Melis, Gian Benedetto; Neri, Manuela; Corda, Valentina; Malune, Maria Elena; Piras, Bruno; Pirarba, Silvia; Guerriero, Stefano; Orrù, Marisa; D'Alterio, Maurizio Nicola; Angioni, Stefano; Paoletti, Anna Maria
ABSTRACT: Introduction : Suppression of sex-steroid secretion is required in a variety of gynecological conditions. This can be achieved using gonadotropin releasing hormone (GnRH) agonists that bind pituitary gonadotropin receptors and antagonize the link-receptor of endogenous GnRH, inhibiting the mechanism of GnRH pulsatility. On the other hand, GnRH antagonists immediately reduce gonadal steroid levels, avoiding the initial stimulatory phase of the agonists. Potential benefits of GnRH antagonists over GnRH agonists include a rapid onset and reversibility of action. Older GnRH antagonists are synthetic peptides, obtained by modifications of certain amino acids in the native GnRH sequence. They require subcutaneous injections, implantation of long-acting depots. The peptide structure is responsible for histamine-related adverse events and the tendency to elicit hypersensitivity reactions. Areas covered : Research has worked towards the development of non-peptidic molecules exerting antagonist action on GnRH. They are available for oral administration and may have a more beneficial safety profile in comparison with peptide GnRH antagonists. This article focuses on the data of the literature about elagolix, a novel non-peptidic GnRHantagonist, in the treatment of endometriosis. Expert opinion : Elagolix demonstrated efficacy in the management of endometriosis-associated pain and had an acceptable safety and tolerability profile. However, further studies are necessary to evaluate its non-inferiority in comparison with other endometriosis's treatments.